Cardiac tamponade as an initial manifestation of systemic lupus erythematosus in early childhood. Issue 2 (February 1992) - Gulati, S; Kumar, L
Abstract : Cardiac tamponade is rare as an initial manifestation of systemic lupus erythematosus (SLE), and even more so in paediatric patients. This paper reports an 8 year old girl with SLE with several unusual features: unusual age of presentation, unusual initial organ manifestation and recurrent cardiac tamponade as a complication.